Network Variability Impacts Mobile Application Performance - et. al., S Alex David, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Internet connectivity became a mandatory on mobile device in recent days. Due to memory constrain and dynamic data management developers were going for the web application or hybrid application development approach for the morden mobile applications. Web applications completely depend on the internet and hybrid applications partially depend on internet. For both cases the network connectivity is mandatory. This paper aim to compare the different speed of the network and based on that what is the impact of the mobile application performance has been analysed.